The Complete Prose of T. S. Eliot: The Critical Edition : Literature, Politics, Belief, 1927-1929 - Eliot, T. S. (Thomas Stearns), 1888-1965 (Project Muse, 2015)
In 1927, T.S. Eliot was baptized and confirmed in the Church of England and became a naturalized British citizen. The works collected in Literature, Politics, Belief are contemporaneous with Eliot's conversion and exhibit his deepening interest in the history, complexity, and difficulty of belief. In addition to the nine essays Eliot collected in his third volume of criticism, For Lancelot Andrewes (1928), Literature, Politics, Belief includes Eliot's reviews of detective novels and an edition of The Complete Sherlock Holmes Short Stories; his review of a two-volume biography of Edgar Allan Poe; and his introduction to Ezra Pound's Selected Poems.